Pros and Cons of In-Service Teacher Professional Development via Observation of Filmed Classes - Cohen Zada, Oren; Bueno Villaverde, Ángeles (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2021)
Filming lessons is one of the most common and effective tools in teacher professional improvement and development. In-depth interviews with 60 teachers in Israel Southern District reveal their experience with filmed lessons in professional development. This qualitative constructivist study showed that the main reason for teachers' objection to lesson filming is that the camera affects the processes occurring in the classroom. The study further demonstrated that filmed lessons significantly enhance insights into processes of learning and instruction and advance teachers' reflection on their practice.